Effect of Employee Empowerment on Skilled Workers’ Job Performance and Personal Commitment in Manufacturing Companies - S. Gowri, M.Umamaheswari, R. Maheswari,M.Muthuselvi, M. Venkatesh Kumar, . Gowthami T (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study investigates the dynamic relationship between employee empowerment, individual commitment, and job performance among skilled employees in manufacturing companies. The research explores the extent to which empowerment initiatives influence the dedication and performance levels of skilled workers in the manufacturing sector. Through a comprehensive analysis of survey data and empirical evidence, the study reveals a positive correlation between employee empowerment and both individual commitment and job performance. Skilled employees who perceive themselves as empowered demonstrate heightened commitment to their roles and contribute positively to overall job performance. The findings underscore the strategic importance of fostering an empowered work environment within manufacturing companies to cultivate a dedicated and high-performing workforce. As organizations seek to optimize their operations in the competitive manufacturing landscape, understanding and leveraging the impact of employee empowerment can serve as a key driver for sustained success and employee satisfaction.